The Role of International Monetary Fund (IMF) Programs in Promoting Gender Equality - Safaruddin Harefa (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2025)
This study examines the role of the International Monetary Fund (IMF) in promoting gender equality within its macroeconomic stabilization programs. It analyzes whether the IMF’s gender mainstreaming strategy genuinely advances women’s economic empowerment or remains constrained by traditional fiscal discipline and market-oriented objectives. Using a qualitative literature review, the paper synthesizes academic studies, IMF policy documents, and institutional reports published between 2015 and 2024, the period during which gender was formally integrated into IMF frameworks. Rather than producing new statistical analysis, this research reviews existing empirical evidence to assess how IMF-supported reforms influence gender outcomes. The findings indicate that although the IMF increasingly recognizes gender equality as “macro-critical” and has introduced tools such as gender-responsive budgeting and gender impact assessments, implementation remains uneven. In several low- and middle-income countries undergoing fiscal consolidation, particularly those heavily dependent on public-sector employment and limited social protection systems, austerity measures have reduced spending in health, education, and childcare—sectors crucial to women’s labor force participation. While gender-focused initiatives show potential, their effectiveness depends on institutional capacity and political commitment at the national level. The study concludes that meaningful progress requires a structural shift from austerity-centered stabilization toward inclusive macroeconomic governance, including counter-cyclical social spending, sustained investment in care infrastructure, and systematic integration of gender metrics into fiscal policy to strengthen long-term economic resilience and equitable development. Keywords:  Empowerment, Fiscal Policy, Gender Equality, Imf, Macroeconomics JEL : J16, F33, H50